Answers

The Brainliest Answer!
2014-09-04T22:01:41+05:30
 Let  p ( x ) =  x^100  and  q ( x ) =  x^2  – 3x  + 2 = ( x  – 1) ( x  – 2)
When p(x) is divided by q(x), then by division algorithm there exists Q(x) and R(x) such that
  p(x)=q(x)+r(x)
x^100=(x-1)(x-2)q(x)+(Ax+B)
put x=1 and x=2
1=A+B and 2^100=2A+B
by solving
A=2^100-1
B=2-2^100
then rem will be...
(2^100-1)x+(2-2^100)
1 5 1
What's the answer?????
Well,the answer as per the nstse book is 2^100(x-1)-(x-2)
both are correct... in my ans... expand my ans...u will get ur ans
2^100 X-X+2-2^100=2^100(X-1)-(X-2)